Knowledge Infrastructure, Process and the Effectiveness of Manufacturing SMEs in Selangor, Malaysia - C. A. Malarvizhi; Abdullah Al- Mamun; Muthiah Prabadevi; Noorshella Che Nawi; Amin Rasti; P. Yukthamarani Permarupan (2015)
Introduction- In today’s competitive business environment, companies are always looking for ways to improve employees’ speed and efficiency. However, the nature of knowledge work is more complex, and therefore more difficult to evaluate. Knowledge workers think and behave differently, and have different needs (Hollar et al. 2002). Organizations whose success or failure is determined by the decisions they make are handicapped by systems that are centered on processes or functions. They face many challenges in today’s business climate. As a result, these organizations struggle to improve business productivity while managing costs and find it hard to make changes in their systems quickly, despite a pressing need to do so. To succeed, these organizations need to move their thinking from processes and functions to decisions; (Andreeva and Kianto, 2012)